5-HTTLPR×interpersonal stress interaction and nonsuicidal self-injury in general community sample of youth. Issue 3 (28th February 2015) - Hankin, Benjamin L.; Barrocas, Andrea L.; Young, Jami F.; Haberstick, Brett; Smolen, Andrew
Abstract: No research with youth has investigated whether measured genetic risk interacts with stressful environment (G⁎E) to explain engagement in non-suicidal self-injury (NSSI). Two independent samples of youth were used to test the a priori hypothesis that the Transporter-Linked Polymorphic Region (5 -HTTLPR ) would interact with chronic interpersonal stress to predict NSSI. We tested this hypothesis with children and adolescents from United States public schools in two independent samples ( N ׳s=300 and 271) using identical procedures and methods. They were interviewed in person with the Self-Injurious Thoughts and Behaviors Interview to assess NSSI engagement and with the UCLA Chronic Stress Interview to assess interpersonal stress. Buccal cells were collected for genotyping of 5 -HTTLPR . For both samples, ANOVAs revealed the hypothesized G⁎E. Specifically, short carriers who experienced severe interpersonal stress exhibited the highest level of NSSI engagement. Replicated across two independent samples, results provide the first demonstration that youth at high genetic susceptibility (5- HTTLPR ) and high environmental exposure (chronic interpersonal stress) are at heightened risk for NSSI. Highlights: We examine for the first time whether genetic risk affects the link between chronic interpersonal stress and nonsuicidal self-injury (NSSI) in youth. We tested this G*E with a discovery sample and then an independent replication sample. Youth with severe interpersonal stress and who have at least one short allele of 5-HTTLPR showed the highest level of NSSI. Data support a genetic vulnerability-stress model of NSSI in youth.